Pandemic-related Restrictions on Freedom of Expression. Nihil novi sub sole? - Górski, Marcin (Pécs journal of international and European law, 2021)
This paper presents some normative and/or factual restrictions impacting the freedom of expres- sion resulting from the COVID-19 pandemic against the background of the norms of internation- al human rights law, more specifically limitation and derogation clauses. These restrictions are categorised according to different criteria. Analysis of the recent practice of the European Court of Human Rights referring to the circumstances related to the COVID-19 pandemic is presented. The paper concludes that so far there are no reasons to assume that the interpretative standards on limitation clauses, developed prior to the pandemic, shall be reformulated to adapt them to the pandemic circumstances.